DESAIN GEOMETRI PELEDAKAN ANDESIT DENGAN METODE THE MODERN TECHNIQUE OF ROCK BALASTING: GEOMETRY DESIGN OF ANDESITE BLASTING USING THE MODERN TECHNIQUE OF ROCK BALASTING METHOD - Yulius Ganti Pangkung (JISTECH: Journal of Information Science and Technology, 2014)
Blasting geometri design using The Modern Techque Of Rock Blasting Method given result of burden (B) 2.621cm, space (S) 3.276 cm , stemming (T) 2.621 cm, sud drilling (U) 0.9 cm, scooting depth 13.629 cm, grade 100- 150, higth of bench 12.285 cm. from the design resulting in blast production of 1051.338 ton, powder factor of and explosive material use is 1589.751 kg/m3 whith the maximum fragmentation size of 28.02 cm